Experiencing part-whole relations of numbers in a partitioning task - Kullberg, Angelika; Nord, Maria (NOMAD Nordic Studies in Mathematics Education, 2025)
The experience of part-whole relations has been identified as being of importance for the development of proficient counting strategies. In an intervention in first grade (seven-year-olds), one activity was about partitioning numbers in different ways using finger patterns. We analyzed the enactment of the activity using variation theory as a theoretical framework, and identified critical aspects for students’ learning: to differentiate between finger pattern and finger number, to differentiate between parts and fingers, to make parts bigger than 1, to experience commutativity, and to see zero as one part. The findings provide new knowledge about what needs to be discerned by students in order to be able to partition numbers up to 10, using finger patterns for illustrating part-whole relations.